Promoting children's inquiry performances in alternate reality games: A mobile concept mapping‐based questioning approach - Liang, Hsin‐Yi; Hsu, Tien‐Yu; Hwang, Gwo‐Jen (British journal of educational technology, 2021)
Active inquiry plays a key role in science education. To facilitate children's motivation, alternate reality games are applied to engage children actively in inquiry in authentic learning contexts. However, the complexity of real‐world contexts and the ambiguity of game puzzles increase the difficulty for children to conduct effective inquiries. To achieve successful inquiry‐based learning, concept mapping is an effective learning strategy to guide children to organise related information as well as to brainstorm for possible solutions. Accordingly, this study proposes a mobile concept mapping‐based questioning approach for environmental education. A quasi‐experimental study was conducted to evaluate the effectiveness of the proposed approach and the conventional questioning approach in game‐based inquiry‐based learning. The results showed that the proposed approach had a more significant effect on learning achievement, critical thinking, and learning attitude than the conventional questioning approach. However, cognitive overload negatively affected the children's learning. Besides, it was found that improper use of concept maps could limit their creative problem‐solving performances. Practitioner notes What is already known about this topic Alternate reality game (ARG) significantly promotes children’s learning motivation and engagement of game‐based inquiry learning activities. Most children have difficulties in learning with ARGs due to the complexity of real‐world contexts and the ambiguity of the puzzles. Children cannot construct knowledge effectively without proper learning supports in their cognitive process; however, it is challenge to provide proper learning supports without distracting children from gaming. What this paper adds An ARG with a mobile concept mapping‐based questioning approach (ARG‐CMQ) was applied to facilitate meaningful inquiry‐based learning for children in different real environments (school campuses and in science museums). Both quantitative and qualitative analyses were examined to identify the effect of different learning strategies to support children learning with ARGs. ARG‐CMQ improved children’s learning achievement, critical thinking and learning attitude better than conventional ARGs. ARG‐CMQ might limit children’s divergent thinking and influences their creative problem‐solving performance. Implications for practice and/or policy ARG‐CMQ is a potential approach for inquiry‐based learning in real environments, especially in improving learning perceptions and higher‐order cognitive abilities. ARG‐CMQ can be used to support competency‐based education.